PP-50 Population pharmacokinetics and dosing optimisation of latamoxef in neonates. Issue 10 (20th September 2017) - Zhao,
Abstract : Background: Latamoxef, a new broad-spectrum oxac-ephem antibiotic, was used off-label in neonates. The present study aims to evaluate pharmacokinetics of latamoxef in neonates and establish appropriate dosing regimen. Methods: Blood samples were collected from neonates treated with latamoxef and concentrations were quan-tified by HPLC-UV. Population pharmacokinetic analysis was performed using NONMEM software. Results: A total of 42 neonates were recruited. A one-compartment model with first-order elimination showed the best fit with the data. Current weight and postmenstrual age were identified as significant covari-ates on clearance. Current weight was identified as a sig-nificant covariate on volume of distribution. The reliability and stability of the population pharmacokinetic model was evaluated by bootstrap and normalised predictive distribution error. Conclusion: The population pharmacokinetics of lata-moxef was evaluated in neonates and an optimal dosing regimen was established.